Kajian Spesifikasi Arah Kebijakan Pembangunan Kota Purwokerto - Anwaruddin Anwaruddin (JIANA ( Jurnal Ilmu Administrasi Negara ), 2009)
Purwokerto city in global era progressively have to start to build competitive capabilities amongother Kabupaten/ Kota. Purwokerto City have to can identify strength, weakness, opportunity andthreat able to be allowed for Purwokerto design in harmony with available potency. Beside that, thiscity design have to in harmony with public interest of Purwokerto. Specification developmentstudies of Purwokerto City is required to harmonize analysis of SWOT with public interest. So that,in the future urban development can comprehend rationally and democratic by public in local level.The result of purwokerto city analyse indicate that Purwokerto city can be developed as educationcity, services and commerce city.